Wheat peptides as catalysts for athletic performance improvement in cross-country skiers: A randomized controlled trial - Xiang, M.; Han, Q.; Chen, Y.; Duan, S.; Han, X.; Sui, X.; Ren, C.; Wang, Q. (Metabolites, 2024)
Objectives: This study investigated the efficacy of wheat peptide supplementation compared to regular proteins in elite cross-country skiers, providing insights into the metabolic and performance effects of these supplements in order to guide athletes in selecting optimal energy sources for training and competition.